2020
DOI: 10.34172/ijbsm.2020.27
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Eight Weeks of Testosterone Enanthate Consumption on Oxidative Indicators of Kidney Tissue in Resistance Trained Rats

Abstract: Introduction: Taking anabolic steroids can affect the state of oxidative stress in different tissues of the body such as kidneys. This study aimed to examine the effect of 8 weeks of resistance training with testosterone enanthate consumption on tissue oxidation indicators in male rats. Methods: In the current experimental study, 18 rats with an average weight of 250 ± 50 g were divided into 3 groups of 6 animals including: (1) control, (2) training, and (3) training + testosterone. Rats in the training and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Studies on the toxic effects of AASs on the liver have shown that the NF-κB pathway can also be activated by steroids in a manner independent of oxidative stress and thus plays a protective role in counteracting the pro-apoptotic effect of AASs on hepatocytes [ 52 , 53 ]. Studies in rats have shown that resistance training combined with testosterone intake increases the expression of the NF-κB pathway and cyclooxygenase 2 (COX-2) genes, related to inflammation in the kidneys [ 54 ]. Furthermore, the NF-κB pathway can be activated by boldenone-induced oxidative stress, leading to the transcription of pro-inflammatory genes and thus the accumulation of pro-inflammatory factors such as TNFα and IL-1β [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the toxic effects of AASs on the liver have shown that the NF-κB pathway can also be activated by steroids in a manner independent of oxidative stress and thus plays a protective role in counteracting the pro-apoptotic effect of AASs on hepatocytes [ 52 , 53 ]. Studies in rats have shown that resistance training combined with testosterone intake increases the expression of the NF-κB pathway and cyclooxygenase 2 (COX-2) genes, related to inflammation in the kidneys [ 54 ]. Furthermore, the NF-κB pathway can be activated by boldenone-induced oxidative stress, leading to the transcription of pro-inflammatory genes and thus the accumulation of pro-inflammatory factors such as TNFα and IL-1β [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%